Developing Sadhu Lima Villa in Pererenan, Badung, Bali - Fitri Hartini; I Gede Mudana; I Ketut Sutama; Kadek Ayu Dwi Juliasri; I Ketut Suparta (Badan Riset dan Inovasi Daerah Provinsi Bali, 2026)
Purpose: This study examines the development of Sadhu Lima Villa in Pererenan, North Kuta, Badung, Bali, and designs a villa development model applicable to similar boutique property projects. Research methods: A qualitative case study approach was employed, utilizing observation, semi-structured interviews with key stakeholders (investor, architect, contractor, and villa manager), focus group discussions (FGDs), and document analysis. The POAC (planning, organizing, actuating, and controlling) framework served as the analytical lens to evaluate the managerial process. Results and discussion: Sadhu Lima Villa was developed with a strong emphasis on tropical-modern architecture, eco-conscious design, and market-oriented strategies. Financial feasibility analysis confirmed its profitability, with a positive Net Present Value (NPV), a payback period of less than four years, and an annual Return on Investment (ROI) exceeding 50%. Furthermore, a comprehensive development model was designed, comprising three key components: design, finance, and sustainability. Implication: The study contributes to applied tourism business planning by providing insights into the creation of small-scale accommodation projects equipped with systematic business models.